How Successful in Individual Prosumer Performance in Thailand - Sa-Ardnak, Arissa; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2021)
The evolution of technology has affected consumer behavior around the world, including through faster, more frequent data consumption, data comparison, and more self-specific needs. This makes consumers more keenly focused on self-production. The prosumer society is plentiful and focuses on effectiveness. This results in greater quality control problems. The usage of those who do not yet value it are less clear. Workers are not paid for their work, unlike other economies. The prosumer shares their knowledge in a way which is fulfilling. A professional prosumer shares their knowledge with society that makes them proud. The technology usage will help improve individual prosumers' key to success. This study offers a conceptual framework of factors that affect individual prosumer performance. This article synthesizes Technology Cultural Theory (TCT) based on TAM2, Information System Success Model (ISS) based on the IS success model, Prosumer Theory (PT) based on consumer behavior, and Individual Prosumer Performance (IPP) based on individual performance.
Keywords: creativity; individual performance; prosumer; self-efficacy; technology